Clinical trials of bispecific antibody therapy for colorectal cancer: advanced and next steps - Shao, Wen; Liu, Yuhang; Huang, Lina; Lu, Sihan; Zhai, Yixiang; Xiong, Yue; Chen, Nuojun; Ye, Pengcheng; Lv, Qijun (Frontiers in Oncology, 2026)
BackgroundColorectal cancer (CRC) is a malignant tumor with a high incidence and mortality rate worldwide. The existing treatment methods have limitations in terms of efficacy or applicable population. Bispecific antibodies (BsAbs) can simultaneously target two different antigens and are expected to overcome tumor immune escape, providing a new strategy for the treatment of CRC.MethodThis study systematically retrieved clinical trial registration platforms such as Trialtrove and ClinicalTrials.gov up to July and November 2025, and collected trial data on the treatment of CRC with BsAbs. Descriptive analyses were conducted on key indicators such as the stage distribution, primary endpoints, funding types, global distribution, and target combinations of the trials by establishing clear inclusion and exclusion criteria.ResultA total of 192 clinical trials were included. Since 2018, the number of related trials has significantly increased, and the trial phase has shifted from mainly Phase I in the early stage to a substantial growth in Phase II and Phase III trials after 2023-2024. The primary endpoints of the trial were highly concentrated on safety assessment (such as safety/tolerability, adverse events). The industrial sector is the main funder (68.3%), and the number of trials conducted in China (n=125) ranks first in the world. The target combinations are most commonly PD-1/CTLA-4 and PD-1/VEGF, and studies on novel combinations such as EGFR/cMET are also on the rise. Efficacy data from key trials (e.g., Cadonilimab, Amivantamab) demonstrate encouraging response rates in both locally advanced and metastatic settings, particularly in MSS/pMMR populations.ConclusionThe clinical research and development activities of BsAbs in the field of CRC treatment are becoming increasingly active and mature. Currently, the focus is on establishing a safety profile. Dual-target blocking based on PD-1 and strategies targeting EGFR/cMET are the current main research and development directions. In contrast to resource-intensive CAR-T or payload-driven ADCs, BsAbs provide a ready-to-use therapeutic format that simultaneously engages two antigens, offering distinct practical and mechanistic benefits. In the future, it is necessary to further optimize the design of BsAbs, explore combination therapies and identify predictive biomarkers to promote its clinical transformation and improve the prognosis of CRC patients.